Species Identification of Mycobacteria by PCR-Restriction Fragment Length Polymorphism of the rpoB Gene - Lee, Hyeyoung (American Society for Microbiology, 2000)
PCR-restriction fragment length polymorphism analysis (PRA) using the novel region of the rpoB gene was developed for rapid and precise identification of mycobacteria to the species level. A total of 50 mycobacterial reference strains and 3 related bacterial strains were used to amplify the 360-bp region of rpoB, and the amplified DNAs were subsequently digested with restriction enzymes such as MspI and HaeIII. The results from this study clearly show that most of the mycobacterial species were easily differentiated at the species level by this PRA method. In addition, species with several subtypes, such as Mycobacterium gordonae, M. kansasii, M. celatum, and M. fortuitum, were also differentiated by this PRA method. Subsequently, an algorithm was constructed based on the results, and a blinded test was carried out with more than 260 clinical isolates that had been identified on the basis of conventional tests. Comparison of these two sets of results clearly indicates that this new PRA method based on the rpoB gene is more simple, more rapid, and more accurate than conventional procedures for differentiating mycobacterial species.